Ageing population and urban spaces – New digital challenges for elderly well-being - Maria Rosario Chaza Chimeno; Rosaria Revellini; Cristiana Cellucci (Agathón)
The essay proposes a critical reading of some of the main issues currently underway globally concerning the growing percentage of elderly people living in urbanised contexts affecting their well-being. Looking at urban complexity with respect to the elderly cohort means investigating the constant evolution of the person-environment relationship and the existing limits, as well as the negative consequences of climate change and its influence on the health of frail subjects. In relation to these dynamics, digitalisation is identified as a transversal challenge that can support active and healthy ageing. The contribution addresses the issues emerging from the reference literature, highlighting critical issues and potentialities concerning the coexistence of these themes for possible future research scenarios in the field of technological and environmental design.